(untitled) (Herald of the National Children’s Medical Center, 2024)
A cyst of the common bile duct (cysts) is a rare pathology found in childhood surgery. Congenital dilation of the bile ducts leads to their obstruction, accounting for about 1% of all benign diseases of the bile ducts. Its prevalence is 1 case per 15,000 live births, with the main prevalence in Asian countries. Among the patients of children with FGM, 40% are girls. At the same time, the disease is most common in Eastern countries (1 per 1000 population), less often in Europe (1 per 100,000) and America (1 per